Development of statistical approaches to the handling and analysing of large occupational data sets - Thompson, John (Sudbury, 2005)
"Methods were developed to extract and prepare data from large complex occupational exposure databases, to undertake statistical explorations and analyses relating to possible changes in exposure patterns that may have been influenced by the impact of legislation and changes in regulatory exposure limits. A database compiled from exposure measurements collected over a 30-year period, primarily from iron and steel foundries throughout the UK, was used as the example with which to develop and test the statistical methods. These methods were then applied to develop and test hypotheses about the impact on exposure patterns of respirable silica and dust. These explorations and analyses showed that there were significant reductions in exposures to these hazardous substances, especially in the upper exposure ranges, demonstrating the valuable impact of both legislation and the tightening of regulatory limits and the importance of monitoring in demonstrating this sustained impact in reducing exposure risks. ..."